Figure 4 from: Stur E, Borkent A (2014) When DNA barcoding and morphology mesh: Ceratopogonidae diversity in Finnmark, Norway. ZooKeys 463: 95-131. https://doi.org/10.3897/zookeys.463.7964 - Stur, Elisabeth; Borkent, Art (Zenodo, 2014)
Figure 4 - A, B Forcipomyia sp. 5 female A terminalia, in ventral view B head, in anterior view C, D Forcipomyia sp. 4 female C terminalia, in ventral view D head, in anterior view.